Solar Energy 2004
DOI: 10.1115/isec2004-65087
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis of Active and Passive Building Thermal Storage Utilization

Abstract: Cooling of commercial buildings contributes significantly to the peak demand placed on an electrical utility grid. Time-of-use electricity rates encourage shifting of electrical loads to off peak periods at night and on weekends. Buildings can respond to these pricing signals by shifting cooling-related thermal loads either by precooling the building’s massive structure or by using active thermal energy storage systems such as ice storage. While these two thermal batteries have been engaged separately in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The thermal storage system could contribute as much as 20-30% electrical peak load reduction [113]. In the study of Henze et al [114] and Zhou et al [115], up to 26% of energy cost can be saved by using the thermal storage systems for shifting peak loads.…”
Section: Control Of Energy Storage Systemsmentioning
confidence: 99%
“…The thermal storage system could contribute as much as 20-30% electrical peak load reduction [113]. In the study of Henze et al [114] and Zhou et al [115], up to 26% of energy cost can be saved by using the thermal storage systems for shifting peak loads.…”
Section: Control Of Energy Storage Systemsmentioning
confidence: 99%
“…In and Zhou et al (2005), different combinations of the active and/or passive thermal storage systems for shifting peak loads were also investigated. Results showed that active plus passive thermal storage systems can save energy cost up to 26% compared with the case without thermal storage.…”
Section: Building Thermal Massesmentioning
confidence: 99%
“…highperformance buildings, distributed generation, and demand response [2], [3], and • Novel storage technologies e.g. electric drive vehicles and thermal storage [4]- [6]. These technologies introduce new dynamics across multiple timescales, forcing power systems planners and policy makers to revisit the longstanding question of how much operational detail must be captured to adequately assess long-term planning options.…”
Section: Introductionmentioning
confidence: 99%